2015
DOI: 10.4314/ajtcam.v12i1.4
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity of <i>Clausena anisata</i> hook, a South African medicinal plant

Abstract: Background: Clausena anisata Hook also known as Iperepesi in Xhosa language is a medicinal plant used traditionally for the treatment of various ailments and some opportunistic infections associated with tuberculosis (TB). Patients in South Africa based on the phytotherapeutic information on this species in the Eastern Cape, use this medicinal plant. Hence, the antibacterial activity of various solvent extracts of the leaves and barks were respectively, evaluated using selected bacterial strains. Method: The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…However, Phytosterols were found only in S. incanum extracts. Previous studies indicated that the avonoids, glycosides, tannins, saponins and phenolics were positively tested in the leaves of Nicotiana tabacum L (38), leaves of Withania sominifera (39), roots of Rumex nepelensis (40), leaves of Carica papaya (41) and stem of Clausena ansita (42); which is similar to our result demonstrating the presence of avonoids, glycosides, tannins, saponins and phenolics. The presences of those phytochemicals in different extracts were an indication of that extracts have antibacterial activity and can be used as alternative medicine.…”
Section: Discussionsupporting
confidence: 92%
“…However, Phytosterols were found only in S. incanum extracts. Previous studies indicated that the avonoids, glycosides, tannins, saponins and phenolics were positively tested in the leaves of Nicotiana tabacum L (38), leaves of Withania sominifera (39), roots of Rumex nepelensis (40), leaves of Carica papaya (41) and stem of Clausena ansita (42); which is similar to our result demonstrating the presence of avonoids, glycosides, tannins, saponins and phenolics. The presences of those phytochemicals in different extracts were an indication of that extracts have antibacterial activity and can be used as alternative medicine.…”
Section: Discussionsupporting
confidence: 92%
“…The bacteria and fungi used in this study were chosen primarily on the basis of their importance as opportunistic pathogens of humans infected with TB. [ 12 22 24 ] Strains from the American Type Culture Collection (ATCC) were used for both assays. The bacteria used include four Gram-positive and Gram-negative bacteria, namely, Staphylococcus aureus ATCC 29213, Bacillus cereus ATCC 10702, Enterococcus faecalis ATCC 29212, Streptococcus pyogenes , Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC 100031, Escherichia coli ATCC 8739, and Salmonella typhimurium ATCC 13311.…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 18 20 ] Several researchers have investigated the antibacterial and antifungal activity of medicinal plants used for the treatment of TB in the province. [ 21 22 ] However, no study has been reported on the antimicrobial effect of polyherbal remedies used for the treatment of TB. Since opportunistic bacterial and fungal pathogens tend to cause diseases in TB patients, the study was, therefore, aimed at evaluating the antimicrobial effect of polyherbal medicines used for the treatment of TB in the Eastern Cape Province of South Africa, in other to determine whether they could also serve as antibacterial and antifungal agents.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicine, which involves the use of various plant extracts, serves as an alternative therapy. The folkloric use of many plants is highly valued, including Clausena anisata leaves for the treatment of respiratory tract infections and other bacterial diseases [40], Enantia chlorantha bark for antiviral effects [81,82], Citrus aurantifolia fruit for the management of cardiovascular system conditions [94,95], Azadirachta indica oil for anti-stimulant effect [103], Blighia sapida leaves for the treatment of diarrhoea and cutaneous infection [111], among a great many others. As it was reported by Ahmad et al [41] and Panda et al [110], there is a growing trend in the production of herbal formulations obtained from medicinal plants and minerals for the treatment of different ailments in many countries due to their acceptability as a result of their natural source, synergistic product and supposedly limited side effects.…”
Section: Herbal Medicine and Polyherbal Mixturesmentioning
confidence: 99%